Meeting the technology standards for language teachers - Cornelia Tschichold (CALL communities and culture – short papers from EUROCALL 2016. Edited by Salomi Papadima-Sophocleous, Linda Bradley, Sylvie Thouësny., 2016)
The starting point for this project was the question in how far a Computer-Assisted Language Learning (CALL) module in a Teaching English to Speakersof Other Languages (TESOL) course can bring the students up to the requiredlevel of being confident CALL users. The teachers’ part of the TESOL TechnologyStandards Framework was chosen as evidence for the level of training required.Each standard was first matched against the components of an existing CALLmodule. Standards that were not met were then filtered for achievability in a preserviceteacher training situation. Next, all remaining standards were examined tofind out whether they could be incorporated into the module, either by modificationof an existing element or the introduction of new elements. A second step involvedthe evaluation of components of the CALL course that did not seem to contribute tohelping the students reach any of the technology standards. One of the goals of thisprocedure was to give more structure to the process of regular updates of the modulecontent, beyond simply updating the software used in the module, and to allow for amore principled improvement of the module over the years.